2013
DOI: 10.3389/fpsyg.2013.00575
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to a multisensory speech illusion in older persons is driven by perceptual processes

Abstract: Recent studies suggest that multisensory integration is enhanced in older adults but it is not known whether this enhancement is solely driven by perceptual processes or affected by cognitive processes. Using the “McGurk illusion,” in Experiment 1 we found that audio-visual integration of incongruent audio-visual words was higher in older adults than in younger adults, although the recognition of either audio- or visual-only presented words was the same across groups. In Experiment 2 we tested recall of senten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…Both the elderly and MCI groups in fact displayed numerically greater visual bias that was characterized by a greater proportion of purely visual responses compared to the young group, suggesting the presence of a greater influence of discrepant visual information in the two older groups. These findings are not surprising given the greater reliance of older adults on supportive context when listening to speech [67], and are consistent with previous studies indicating an enhanced McGurk effect [68,69] that may be associated with a greater reliance on visual speech information in healthy elderly. Adults with age-related deterioration in the auditory system will have familiarity with using other contextual cues (including lip-reading) to help disambiguate auditory speech information.…”
Section: Discussionsupporting
confidence: 91%
“…Both the elderly and MCI groups in fact displayed numerically greater visual bias that was characterized by a greater proportion of purely visual responses compared to the young group, suggesting the presence of a greater influence of discrepant visual information in the two older groups. These findings are not surprising given the greater reliance of older adults on supportive context when listening to speech [67], and are consistent with previous studies indicating an enhanced McGurk effect [68,69] that may be associated with a greater reliance on visual speech information in healthy elderly. Adults with age-related deterioration in the auditory system will have familiarity with using other contextual cues (including lip-reading) to help disambiguate auditory speech information.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, this study also showed that this effect was driven by a change in sensitivity (d’) as opposed to response bias, which can also change in aging [70]. Similar results have been shown with the McGurk Effect, where age-related changes in the reported percept are accounted for by changes in perception specifically, as opposed to a more cognitively mediated response bias [71]. …”
Section: Introductionsupporting
confidence: 73%
“…These find ings are in contrast to what would be predicted by the principle of inverse effectiveness (Meredith and Stein, 1983) whereby multisensory enhancement is more pronounced when individual sensory inputs are less effective. More over, it has been shown that for some tasks, performance of older adults is more affected by the presence of distracting or irrelevant cross-modal infor mation relative to that of younger adults (Andres et al, 2006;Poliakoff et al, 2006;Setti et al, 2013). For example, Poliakoff et al (2006) found that older adults' ability to judge the location of a vibrotactile stimulus was more nega tively affected by the presence of a visual distractor compared to young adults.…”
Section: Introductionmentioning
confidence: 99%